Efficiency Prediction and Performance Characterization of Photovoltaic Solar Panel at Baghdad Climate Conditions - Abbas Hamid Sulaymon (Al-Khwarizmi College of Engineering – University of Baghdad, 2013)
The performance of a solar cell under sun radiation is necessary to describe the electrical parameters of the cell. The Prova 200 solar panel analyzer is used for the professional testing of four solar cells at Baghdad climate conditions. Voltage -current characteristics of different area solar cells operated under solar irradiation for testing their quality and determining the optimal operational parameters for maximum electrical output were obtained. A correlation is developed between solar cell efficiency h and the corresponding solar cell parameters; solar irradiance G, maximum power Pmax, and production date P. The average absolute error of the proposed correlation is 5.5% for 40 data points. The results also show that the new solar panels have the highest efficiency compared with the older ones.